Effects of Sub-soil Drip Fertigation on Sugarcane in Field Conditions - Gui-Fen Chen; Qi-Zhan Tang; Yang-Rui Li; Yu-Yi Huang; Bin Liu; Lin Xu; Hai-Rong Huang (Sugar Tech, 2012)

Over-expression of integrin-linked kinase correlates with aberrant expression of Snail, E-cadherin and N-cadherin in oral squamous cell carcinoma: implications in tumor progression and metastasis - Dan Zhao; Xiu-Fa Tang; Kai Yang; Ji-Yuan Liu; Xiang-Rui Ma (Clinical & Experimental Metastasis, 2012)

A stabilized least-squares imaging condition with structure constraints - Guo-Chang Liu; Xiao-Hong Chen; Jian-Yong Song; Zhen-Hua Rui (Applied Geophysics, 2012)

Microsporogenesis and development of the male gametophyte in Allium senescens L. (Liliaceae) in China - Jiao Zhang; Xiao-Rui Liu; Fei-Xiong Zhang; Jia-Xi Liu (Plant Systematics and Evolution, 2012)

Boron distribution and mobility in navel orange grafted on citrange and trifoliate orange - Gui-Dong Liu; Rui-Dong Wang; Li-Shu Wu; Shu-Ang Peng; Yun-Hua Wang; Cun-Cang Jiang (Plant and Soil, 2012)

Postconditioning with vagal stimulation attenuates local and systemic inflammatory responses to myocardial ischemia reperfusion injury in rats - Qiang Wang; Yi Cheng; Fu-Shan Xue; Yu-Jing Yuan; Jun Xiong; Rui-Ping Li; Xu Liao; Jian-Hua Liu (Inflammation Research, 2012)

Pollen development of Cardiocrinum giganteum (Wall.) Makina in China - Hong-Na Chen; Chun-Hai Zhao; Xiao-Rui Liu; Jia-Xi Liu (Plant Systematics and Evolution, 2012)

Protective effects of Lycium barbarum polysaccharide on neonatal rat primary cultured hippocampal neurons injured by oxygen-glucose deprivation and reperfusion - Chen Rui; Li Yuxiang; Hao Yinju; Zhu Qingluan; Wu Yang; Zhao Qipeng; Wang Hao; Ma Lin; Liu Juan; Zhao Chengjun; Jiang Yuanxu; Wang Yanrong; et al. (Journal of Molecular Histology, 2012)

Effect of yeast polysaccharide on some hematologic parameter and gut morphology in channel catfish (Ictalurus punctatus) - Huiling Zhu; Huiyu Liu; Jing Yan; Rui Wang; Lihe Liu (Fish Physiology and Biochemistry, 2012)

Evaluation of the predatory mite Amblyseius hainanensis (Acari: Phytoseiidae) and artificial rainfall for the management of Brevipalpus obovatus (Acari: Tenuipalpidae) - Da-Rui Zheng; Guang-Hua Liu; Run-Jie Zhang; Andrew G. S. Cuthbertson; Bao-Li Qiu (Experimental and Applied Acarology, 2012)

Regeneration of insulin monomers from amyloid fibrils by a NH3/H2O2 two-step method - Rui Liu; Rongxin Su; Yanjun Yu; Wei Qi; Libing Wang; Zhimin He (Biotechnology Letters, 2012)

The U-Pb chronologic evidence and sedimentary responses of Silurian tectonic activities at northeastern margin of Tarim Basin - JingYan Liu; HaiJun Yang; YongHeng Yang; ZhenZhong Cai; YongQuan Liu; ZhiFeng Rui; ZhenZhen Su (Science China Earth Sciences, 2012)

A standard reaction condition and a single HPLC separation system are sufficient for estimation of monolignol biosynthetic pathway enzyme activities - Jie Liu; Rui Shi; Quanzi Li; Ronald R. Sederoff; Vincent L. Chiang (Planta, 2012)

Individual and combined effects of MDM2 SNP309 and TP53 Arg72Pro on breast cancer risk: an updated meta-analysis - Hongtao Cheng; Biao Ma; Ran Jiang; Wei Wang; Hui Guo; Na Shen; Dapeng Li; Qunzi Zhao; Rui Wang; Pengfei Yi; Yue Zhao; Zeming Liu; et al. (Molecular Biology Reports, 2012)

Construction of self-cloning, indigenous wine strains of Saccharomyces cerevisiae with enhanced glycerol and glutathione production - Rui-Ying Hao; Yan-Lin Liu; Zhao-Yue Wang; Bo-run Zhang (Biotechnology Letters, 2012)

A novel hydrolytic product from flesh of Mactra veneriformis and its bioactivities in calcium supplement - Lingchong Wang; Shiyong Chen; Rui Liu; Hao Wu (Journal of Ocean University of China, 2012)

Influences of shrub vegetation on distribution and diversity of a ground beetle community in a Gobi desert ecosystem - Ji-Liang Liu; Feng-Rui Li; Chang-An Liu; Qi-Jun Liu (Biodiversity and Conservation, 2012)

Involvement of p38MAPK/NF-κB Signaling Pathways in Osteoblasts Differentiation in Response to Mechanical Stretch - Liang Wang; Jian-yu Li; Xi-zheng Zhang; Lu Liu; Zong-ming Wan; Rui-xin Li; Yong Guo (Annals of Biomedical Engineering, 2012)

A new model for cation exchange equilibrium considering the electrostatic field of charged particles - Xin Min Liu; Hang Li; Rui Li; Rui Tian; Jie Hou (Journal of Soils and Sediments, 2012)

Trichoderma biodiversity in China - Rui-yan Sun; Zhi-cheng Liu; Kehe Fu; Lili Fan; Jie Chen (Journal of Applied Genetics, 2012)

Haplotype variations of gene Ppd-D1 in Aegilops tauschii and their implications on wheat origin - Lin Huang; Qing Wang; Lian-Quan Zhang; Zhong-Wei Yuan; Ji-Rui Wang; Huai-Gang Zhang; You-Liang Zheng; Deng-Cai Liu (Genetic Resources and Crop Evolution, 2012)

Regulation of mesenchymal stem cell differentiation and insulin secretion by differential expression of Pdx-1 - Huijuan Yuan; Hongmei Liu; Rui Tian; Jie Li; Zhigang Zhao (Molecular Biology Reports, 2012)

Isolation and Characterization of the Cold-Induced Phyllostachys edulis AP2/ERF Family Transcription Factor, peDREB1 - Lei Liu; Xiao-Lu Cao; Rui Bai; Na Yao; Lu-Bin Li; Cong-Fen He (Plant Molecular Biology Reporter, 2012)

Pharmacological kinetics of BmK AS, a sodium channel site 4-specific modulator on Nav1.3 - Zhi-Rui Liu; Jie Tao; Bang-Qian Dong; Gang Ding; Zhi-Jun Cheng; Hui-Qiong He; Yong-Hua Ji (Neuroscience Bulletin, 2012)

Synthesis of 2-R1-2-(4-(2-fluoroethoxy)benzamido)acetate as potential PET imaging agents - Yong He; Jingli Xu; Hang Liu; Man Feng; Xiao Wang; Rui Ding; Chuanmin Qi; Yurong Chen; Fang Li; Zhao-Hui Zhu; Yong-Hong Dang; Ming Wang; et al. (Medicinal Chemistry Research, 2012)

Gastrin inhibits a novel, pathological colon cancer signaling pathway involving EGR1, AE2, and P-ERK - Ling-Jun Song; Rui-Jun Liu; Zhi Zeng; Seth L. Alper; Heng-Jing Cui; Yang Lu; Lin Zheng; Zhao-Wen Yan; Guo-Hui Fu (Journal of Molecular Medicine, 2012)

Combined effects of a neutrophil elastase inhibitor (sivelestat sodium) and a free radical scavenger (edaravone) on lipopolysaccharide-induced acute lung injury in rats - Tao Yang; Junjie Zhang; Lulu Sun; Xiaoyan Zhu; Jinbao Li; Jiafeng Wang; Hui Chen; Rui Bao; Xiaoming Deng; Jiong Hou; Yujian Liu (Inflammation Research, 2012)

Novel HMW glutenin genes from Aegilops tauschii and their unique structures - Wen-Jie Chen; Zhong-Wei Yuan; Lian-Quan Zhang; Xing Fan; Ze-Hong Yan; Ji-Rui Wang; You-Liang Zheng; Huai-Gang Zhang; Deng-Cai Liu (Genes & Genomics, 2012)

Determination of Geometrical and Structural Representative Volume Elements at the Baihetan Dam Site - Wen Zhang; Jian-ping Chen; Chang Liu; Rui Huang; Ming Li; Ying Zhang (Rock Mechanics and Rock Engineering, 2012)

Distribution and linkage disequilibrium analysis of polymorphisms of MC4R, LEP, H-FABP genes in the different populations of pigs, associated with economic traits in DIV2 line - Zhe Chao; Feng Wang; Chang-Yan Deng; Li-Min Wei; Rui-Ping Sun; Hai-Long Liu; Quan-Wei Liu; Xin-Li Zheng (Molecular Biology Reports, 2012)

Erbin inhibits TGF-β1-induced EMT in renal tubular epithelial cells through an ERK-dependent pathway - Qiaodan Zhou; Rui Zeng; Chuou Xu; Lili Liu; Lin Chen; Pei Kou; Guangchang Pei; Shoujun Bai; Yamin Zhang; Caixia Li; Song Rong; Min Han; et al. (Journal of Molecular Medicine, 2012)

Characterization of the expression profile of calpain-3 (CAPN3) gene in chicken - Zeng-Rong Zhang; Qing Zhu; Yong-Gang Yao; Xiao-Song Jiang; Hua-Rui Du; Yi-Ping Liu (Molecular Biology Reports, 2012)

Preparation and bioevaluation of 99mTc nitrido radiopharmaceuticals with pyrazolo[1,5-a]pyrimidine as tumor imaging agents - Rui Ding; Yong He; Jingli Xu; Hang Liu; Xiao Wang; Man Feng; Chuanmin Qi; Junbo Zhang; Cheng Peng (Medicinal Chemistry Research, 2012)

Oceaniovalibus guishaninsula gen. nov., sp. nov., A Marine Bacterium of the Family Rhodobacteraceae - Keshao Liu; Rui Zong; Qipei Li; Yingnan Fu; Yongle Xu; Yanan Wang; Nianzhi Jiao (Current Microbiology, 2012)

Evaluation of the Use of SCAR Markers for Screening Genetic Diversity of Lentinula edodes Strains - Jing-Yu Liu; Zheng-He Ying; Fang Liu; Xin-Rui Liu; Bao-Gui Xie (Current Microbiology, 2012)

Natural Heritage value of Xinjiang Tianshan and global comparative analysis - Xiaoliang Xu; Zhaoping Yang; Adayi Saiken; Shao Rui; Xinyu Liu (Journal of Mountain Science, 2012)

Calculating the Anisotropic Permeability of Porous Media Using the Lattice Boltzmann Method and X-ray Computed Tomography - Yuan Gao; Xiaoxian Zhang; Pratap Rama; Ying Liu; Rui Chen; Hossein Ostadi; Kyle Jiang (Transport in Porous Media, 2012)

Discovery and study of silver sulfate mineral in S5 from the eastern suburb of Xi’an - JingBo Zhao; JunJi Cao; TianJie Shao; Rui Liu; YingLi Yue; Juan Du (Science China Earth Sciences, 2012)

A New Piezochromic Fluorescence and Aggregation-Induced Emission Compound Containing Tetraphenylethylene and Triphenylamine Moieties with Morphology-alterable Property - Xie Zhou; Hai-yin Li; Zhen-guo Chi; Bing-jia Xu; Xi-qi Zhang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2012)

Gel microbead cultivation with a subenrichment procedure can yield better bacterial cultivability from a seawater sample than standard plating method - Shiqi Ji; Rui Zhao; Qi Yin; Yuan Zhao; Chenguang Liu; Tian Xiao; Xiaohua Zhang (Journal of Ocean University of China, 2012)

Characterization of the expression profiles of calpastatin (CAST) gene in chicken - Zeng-Rong Zhang; Xiao-Song Jiang; Hua-Rui Du; Qing Zhu; Xiao-Cheng Li; Chao-Wu Yang; Yi-Ping Liu (Molecular Biology Reports, 2012)

Implication of genetic variants near TMEM18, BCDIN3D/FAIM2, and MC4R with coronary artery disease and obesity in Chinese: a angiography-based study - Hao Huang; Zhi Zeng; Li Zhang; Rui Liu; Xian Li; Ou Qiang; Yucheng Chen (Molecular Biology Reports, 2012)

Metagenomic analysis of DNA viruses in a wastewater treatment plant in tropical climate - Hideyuki Tamaki; Rui Zhang; Florent E. Angly; Shota Nakamura; Pei‐Ying Hong; Teruo Yasunaga; Yoichi Kamagata; Wen‐Tso Liu (Environmental Microbiology, 2012)
Summary Viruses have been detected in the different stages of wastewater treatment plants (WWTPs) at concentrations of 10 8 –10 10 ml −1 of virus‐like particles (VLPs), 10–1000 times higher than in natural aquatic environments, suggesting that WWTPs can be considered as an important reservoir and source of viruses. This study revealed novel diversity and function with the DNA viral communities in the influent, activated sludge, anaerobic digester, and effluent of a domestic WWTP using metagenomics. WWTP was a very specific environment, with less than 5% of the > 936 000 metagenomic sequences obtained (∼70–119 Mbp per sample) similar to sequences present in other environmental viromes. Many viruses found in the WWTP were novel, resulting in only 82% were shared. These data suggested that VLPs of most viral types could be present between 1 and 30 days in the process before they were discharged. Viruses in WWTP and the discharged ones can have potential impacts on the functioning of the wastewater treatment system and on the dynamics of microbial community in the surrounding aquatic environments respectively.

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)